Ecological Resilience Among English Teachers: Navigating Institutional and Social Challenges - Ayu Febiola; Soni Mirizon; Rita Inderawati (JOLLT Journal of Languages and Language Teaching, 2026)
This study investigates the ecological resilience of English teachers as they navigate institutional and social challenges in a private English course in Palembang, Indonesia. Grounded in Bronfenbrenner's Ecological Systems Theory, the research examines how teachers maintain their professional commitment and well-being through the interplay between personal, institutional, and social systems. Using a qualitative case study design, data were collected from ten senior teachers at Gloria English Course through semi-structured interviews and documentation. Thematic analysis was employed to identify recurring themes related to teachers' resilience across ecological layers. The findings reveal that teachers encounter institutional challenges, including policy inconsistency, excessive workload demands, and limited resources, alongside social pressures from parental expectations and workplace dynamics. Despite these difficulties, teachers demonstrated a strong adaptive capacity through personal strategies, including emotional regulation, self-reflection, and spiritual coping. Social and managerial support, especially collegial collaboration, empathetic leadership, and professional trust, played a vital role in maintaining teachers' motivation and stability. The results emphasize that resilience is not a fixed individual trait but a dynamic process shaped by reciprocal interactions between teachers and their environments. This study enriches the understanding of teacher resilience by emphasizing ecological perspectives within private educational contexts, an area that remains underexplored in Indonesian EFL research. Promoting supportive institutional systems and fostering collaborative work cultures can enhance teachers' resilience, improve well-being, and sustain professional quality in private language education.